2021
DOI: 10.1530/eje-20-0468
|View full text |Cite
|
Sign up to set email alerts
|

DIAGNOSIS OF ENDOCRINE DISEASE: Post-pancreatitis diabetes mellitus: prime time for secondary disease

Abstract: While most people with diabetes have type 2 disease, a non-negligible minority develops a secondary diabetes. Post-pancreatitis diabetes mellitus (PPDM) is an exemplar secondary diabetes that represents a sequela of pancreatitis - the most common disease of the exocrine pancreas. Although this type of diabetes has been known as a clinical entity since the late 19th century, early 21st century high-quality epidemiological, clinical, and translational studies from around the world have amassed a sizeable body of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 78 publications
0
66
0
6
Order By: Relevance
“…, PPDM). PPDM is a sub-type of diabetes of the exocrine pancreas and is caused by acute pancreatitis in four out of five people and chronic pancreatitis in one out of five people[ 12 ]. Its epidemiology, risk factors, pathogenesis, and management were comprehensively reviewed elsewhere[ 12 ].…”
Section: Persistent Hyperglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…, PPDM). PPDM is a sub-type of diabetes of the exocrine pancreas and is caused by acute pancreatitis in four out of five people and chronic pancreatitis in one out of five people[ 12 ]. Its epidemiology, risk factors, pathogenesis, and management were comprehensively reviewed elsewhere[ 12 ].…”
Section: Persistent Hyperglycemiamentioning
confidence: 99%
“…PPDM is a sub-type of diabetes of the exocrine pancreas and is caused by acute pancreatitis in four out of five people and chronic pancreatitis in one out of five people[ 12 ]. Its epidemiology, risk factors, pathogenesis, and management were comprehensively reviewed elsewhere[ 12 ]. A large 2020 cohort study by Cho et al [ 13 ] compared the risks of developing pancreatic cancer in PPDM vs type 2 diabetes mellitus without history of pancreatitis and showed that PPDM was associated with a 7-times significantly higher risk for pancreatic cancer (adjusted hazard ratio 6.94; 95% confidence interval 4.09 to 11.77).…”
Section: Persistent Hyperglycemiamentioning
confidence: 99%
“…Participants who were normoglycaemic before and during attack of AP and had follow-up HbA1c ≥ 5.7% (39 mmol/mol) and/or FPG ≥ 100 mg/dL (5.6 mmol/L) after hospital discharge constituted the NODAP group. Only participants who met the above criteria at more than three months after hospitalisation for AP were included in the NODAP group, in line with the published recommendations [1,2,29].…”
Section: Study Groupsmentioning
confidence: 99%
“…Post-pancreatitis diabetes mellitus, which is a subtype of diabetes of the exocrine pancreas, is the most frequent sequela of acute pancreatitis (AP) [1,2]. Epidemiological evidence showed that individuals with a history of AP are at more than two-times higher risk of developing diabetes mellitus when compared with the general population [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation